EVALUATION OF ANTIBACTERIAL ACTIVITY OF PROSOPIS JULIFLORA (SW.) DC. LEAVES - Thakur, Rupesh; Singh, Rupal; Saxena, Pooja; Mani, Abin (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The ethnobotanical importance of Prosopis juliflora is well-known in the folkloric system of medicine for the treatment of various ailments. Although, the study related to the antibacterial potential of this plant, from Central India is scanty. Material and methods: The in vitro antibacterial activity of Prosopis juliflora leaves collected from the local area was evaluated against ten bacterial type cultures by agar well diffusion assay. The crude extracts prepared by two methods separately with three different solvents were examined for the preliminary antibacterial activity and phytochemical screening, the results of which were used for the choice of solvent and mass extraction of crude extract. Solvent fractionation of crude extract was done employing two sets of solvents namely Set-PCE and Set-HDB which resulted in total, six organic and two aqueous fractions, which were finally subjected to antibacterial activities. Results: Varying degrees of growth inhibition was shown by all the fractions against tested microorganisms. The highest antibacterial activity was observed in aqueous fractions as compared to solvent fractions. Conclusion: Isolation and characterization of the bioactive components can be further done by systematic screening of the most active solvent fraction which could lead to the possible source of new antibacterial agents.